Peran Customer Satisfaction Memediasi Pengaruh Customer Experiences Terhadap Repurchase Intention Pada Pisto Coffee & Eatery (Lembaga Pengembangan Kinerja Dosen, 2024)
Pisto Coffee & Eatery, a café in Denpasar, conducted a study with 110 respondents to explore the role of customer satisfaction in mediating the impact of customer experience on repurchase intention. Data were collected via questionnaires and analyzed using classical assumption tests, path analysis, and mediation testing. The findings indicate that customer experience positively influences repurchase intention and customer satisfaction, while customer satisfaction also positively affects repurchase intention. Additionally, customer satisfaction partially mediates the relationship between customer experience and repurchase intention. This study underscores the importance of Pisto Coffee & Eatery's strategy to enhance customer experience in order to boost customer satisfaction and repurchase intention.